INTERNAL CONTROL IN SALES ACCOUNTING SYSTEM - Indah Permata Sari (Inovasi, 2022)
The importance of internal control in sales recording activities has become a business necessity. Therefore, building an accounting system is a necessity that companies need to build adequate recording facilities, so that company finances are under control. In addition, the internal control system in sales can assist companies in making decisions for business development and improvements. This study aims to describe how the implementation of the company's internal control relates to sales through the accounting system. This study used a qualitative approach with descriptive analysis. The research was conducted at automotive companies in Jakarta. As for the correspondents in this study are those who directly use the sales accounting system. The results of the study suggest that the sales accounting system can be an internal control tool for leaders in seeing the actual level of sales and profits. In addition, the accounting system provides accurate information regarding the company's financial position, thereby helping top management to make decisions/make policies.Keywords: Sales, Accounting-Based Recording System, Internal Control, Automotive